A bibliometric study of aerobic, resistance, and combined aerobic and resistance exercise research in the elderly: insights from WoS using citespace - Changyuan, Zhao; Huibin, Hao; Dev, Roxana Dev Omar (Malque Publishing, 2025)
As the global population ages, exercise interventions have become increasingly important for promoting health in older adults. Aerobic exercise, resistance exercise, and their combination each offer unique benefits. However, the respective research trends of these exercise modalities have rarely been systematically compared. This study aims to provide a comprehensive bibliometric analysis of these three exercise modalities using Web of Science data and CiteSpace visualization. This study retrieved and analyzed literature from the Web of Science Core Collection (2015–2024) using CiteSpace software. The search targeted articles on aerobic exercise (AE), resistance exercise (RE), and combined aerobic and resistance exercise (CARE) for the elderly. After manual screening, 1,465 articles were included (AE: 616; RE: 746; CARE: 103). CiteSpace was employed to construct country collaboration, institutional, co-authorship, and keyword co-occurrence maps, as well as to identify emerging research fronts. The Results show that RE received the highest research attention, peaking in 2019, while AE maintained a stable output. CARE had lower publication volume but showed notable growth. The United States, Brazil, and China were the leading contributors, though international collaboration in combined exercise studies remains weak. Keyword analysis revealed that AE studies emphasized cardiovascular and cognitive benefits, RE focused on muscle function and nutritional support, and CARE highlighted fall prevention, quality of life, and chronic disease management. The field is shifting from single-modality interventions toward integrated, multidimensional strategies. CARE is emerging as a promising approach due to its comprehensive health benefits. However, gaps remain in research collaboration and knowledge structure in this area. This study provides a macroscopic overview of global trends and may inform interdisciplinary research and policy development aimed at healthy aging.